Halal meat and religious slaughter: From spatial concealment to social controversy – Breaching the boundaries of the permissible?. (August 2019) - Lever, John
Across the secular West, the slaughter of animals for food has become an almost clandestine activity. Very occasionally however, when slaughter comes into view, social and political controversy emerges. In this paper, I examine two such episodes in England and the controversies subsequently engendered: the controversy over kosher meat and the Jewish method of slaughter ( shechita ) in the 19th century, and the contemporary controversy over halal meat and the Muslim method of slaughter ( dhabiha ). These controversies are complex and double-edged in that, not only do they involve food, which often invokes anxieties about what is being ingested and what moral boundaries are being crossed, they also involve religion. Both episodes are also linked to periods of rapid migration into the UK, and to concerns about integration and the threats posed to British values and national identity by the food practices of outsiders . However, while concern over kosher meat production and Jewish migrants in the 19th century was largely concealed within the spatial boundaries of Jewish communities, from the late 20th century onwards halal meat has become increasingly visible in line with the demographic expansion of the Muslim population out of racialized community spaces. It is in this context, I contend, in line with a new and emerging geography of religious food practice, that halal meat has breached the boundaries of the permissible to challenge the 'civilized' values underpinning the hegemonic food discourse.